H-RAS mutation is a key molecular feature of pediatric urothelial bladder cancer. A detailed report of three cases. Issue 2 (April 2016) - Castillo-Martin, Mireia; Collazo Lorduy, Ana; Gladoun, Nataliya; Hyun, Grace; Cordon-Cardo, Carlos
Summary: Introduction: Urothelial carcinoma (UC) of the bladder is a rare entity in the pediatric population, with an incidence of less than 0.4% in patients younger than 20 years. These patients overwhelmingly present with non-muscle-invasive low-grade disease and an indolent behavior. Objective: The aim was to determine the source of the different natural history between pediatric population and adults; we hypothesized that pediatric bladder cancer may stem from different molecular pathways. Our objective with this descriptive case series was to study the main genes involved in pediatric urothelial bladder carcinoma using immunohistochemical (IHC) and mutational analysis. By studying the genetic alterations and immunophenotype of the most commonly altered genes in bladder urothelial cancer in three pediatric tumors we could gain better understanding of the molecular pathogenesis in this rare disease. Study design: Formalin-fixed paraffin-embedded (FFPE) tissue slides of urothelial bladder tumors from three pediatric patients were retrospectively identified at Columbia University pathology archives (1990–2011) and re-evaluated. FGFR3, H-RAS, and PI3K hotspots mutational analyses were conducted by polymerase chain reaction amplification and Sanger sequencing from the FFPE tissue blocks. IHC analysis was conducted using antibodies against p53, PTEN, RB, EGFR, and HER2. Proliferative rate was assessed by Ki-67 expression. Results: Two patients had low-grade Ta disease, whereas the other tumor was classified as a papillary urothelial neoplasm of low malignant potential. None of the lesions recurred. Notably, all specimens showed H-RAS G12V mutation, whereas they were characterized by wild-type FGFR3 and PI3K . Nuclear p53 was not detected, whereas PTEN and RB expression were maintained. EGFR was expressed in the three cases and HER2 was negative. The proliferation rate was very low in all cases. Discussion: It is difficult to draw strong conclusions from the study of three tumors treated at the same institution and from the same referral population, and a multicentric study should be performed to confirm these preliminary results. However, we propose that H-RAS mutation analysis could be performed on urothelial bladder tumors of pediatric patients. The knowledge in the molecular basis of urothelial bladder tumors in children opens a promising field which could lead us to establish different guidelines for surveillance and follow-up of pediatric urothelial bladder cancer patients. Conclusion: Pediatric tumors are characterized by a consistent H-RAS mutation status, whereas FGFR3 and p53 pathways are not involved in this tumor initiation. These results may explain the few recurrences seen in this population.